PHOTOLUMINESCENCE SPECTRAL FEATURES OF SILICON NANOWIRES (Jurnal Teknologi (Sciences & Engineering), 2016)
Computer simulation using matlab programming approach is carried out to study the photoluminescence (PL) properties of silicon (Si) nanowires (NWs) with diameter between 1.5 and 5.8 nm. An integrated hybrid model comprising of quantum confinement, surface states, and exciton binding is developed to calculate the size, wavelength and photon energy dependent PL intensity. The influence of size and passivation on the band gap energy and PL spectra of Si nanowires (NWs) are examined. It is observed that all the model parameters for quantum confinement, localized surface states, and exciton energy are responsible for the changes in the electronic and optical properties of Si NWs. The simulated data are compared with experimental findings. The admirable features of the results suggest that the present model is significant for understanding the mechanism of visible PL from Si NWs. The model can be extended to study temperature dependent PL for other nanostructures of different shapes and size.